2008
DOI: 10.1177/1538574407308941
|View full text |Cite
|
Sign up to set email alerts
|

Serum Creatinine Stabilization Following Renal Artery Stenting

Abstract: The impact of renal artery stenting on renal function in a subgroup of consecutive de novo patients with atherosclerotic renal artery stenosis from the single operator, single center, retrospective renal stent trial is defined. Patients with inadequate preprocedure and/or follow-up renal function studies were excluded. Abnormal baseline serum creatinine (sCr) was defined as > or = 1.5 mg/dL. Follow-up sCr was improved, unchanged, or worsened if the variance from baseline decreased by >20%, stayed within 20%, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…22,40-42 Other studies have noted that patients with a recent decline in glomerular filtration rate (GFR) derive the greatest benefit. 25,37,42-44 Bilateral stenting was found to improve or to stabilize renal function in some studies 32,37 but not in others. 16,21,29,38,43-45 Bilateral disease was noted to adversely affect survival, 22,40 whereas baseline stenosis 32 and good left ventricular function 39 were found to be predictors for improved renal function.…”
Section: Article Selection and Review Metricsmentioning
confidence: 99%
See 2 more Smart Citations
“…22,40-42 Other studies have noted that patients with a recent decline in glomerular filtration rate (GFR) derive the greatest benefit. 25,37,42-44 Bilateral stenting was found to improve or to stabilize renal function in some studies 32,37 but not in others. 16,21,29,38,43-45 Bilateral disease was noted to adversely affect survival, 22,40 whereas baseline stenosis 32 and good left ventricular function 39 were found to be predictors for improved renal function.…”
Section: Article Selection and Review Metricsmentioning
confidence: 99%
“…Multiple trials noted protective effects of distal protection devices during RASt. 37,46,47 None of the recent clinical trials (CORAL, ASTRAL, STAR, RAS-CAD) showed improvement in renal function with RASt. The ASTRAL trial reported higher creatinine values at 5 years for both the stenting and medical therapy groups, although higher in the stenting group, but no change or difference was reported.…”
Section: Article Selection and Review Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported our extensive experience with renal artery stenting for atherosclerotic lesions. [8][9][10][11][12] There are only a few studies that have analyzed long-term outcomes after endovascular therapy for RAFMD, therefore, this report will analyze the short and long-term outcomes of patients undergoing endovascular treatment for RAFMD.…”
mentioning
confidence: 98%
“…[6][7][8] Factors affecting the need for target vessel revascularization (TVR) after renal stenting include solitary kidney, stent diameter Ͻ5 mm, age Ͻ67 years, peripheral arterial disease, and stroke. 6 Few studies have analyzed the management of recurrent symptomatic renal in-stent stenosis.…”
mentioning
confidence: 99%